Childhood exposures and deficiencies as determinants of cancer risk in adulthood - Binafsha Manzoor Syed (LIAQUAT MEDICAL RESEARCH JOURNAL, 2025)
Cancer development is increasingly recognized as a life-course process influenced by early-life exposures and nutritional status. During critical periods of growth and development particularly first 1000 days, biological systems are particularly susceptible to carcinogenic insults and epigenetic modifications that may predispose individuals to malignancy later in life. Deficiencies in key nutrients such as folate and vitamin D can impair DNA repair and immune function, while early exposure to environmental toxins and pollutants contributes to genomic instability and endocrine disruption. Additionally, persistent infections—including Hepatitis B (HBV), Human papillomavirus (HPV), and Helicobacter pylori infection—play a significant role in infection-related cancers, particularly in low- and middle-income countries. Socioeconomic disparities further exacerbate these risks by limiting access to nutrition, healthcare, and preventive interventions. Addressing these early determinants through integrated public health strategies—such as improved childhood nutrition, vaccination programs, and environmental regulation—offers a critical opportunity for cancer prevention. A shift toward early-life interventions is essential to reduce the long-term global cancer burden and advance equitable health outcomes.